The larva of Agapetus episkopi Malicky 1972 (Trichoptera: Glossosomatidae), including a key to the larvae of Glossosomatidae of the Hellenic western Balkan region - Waringer, Johann; Karaouzas, Ioannis (Zootaxa, 2017)
In this paper, we present a description of the previously unknown larva of Agapetus episkopi Malicky 1972 (Trichoptera: Glossosomatidae). Information on the morphology of the larvae is given and the most important diagnostic features are photographed. As a species of subfamily Agapetinae Martynov 1913, A. episkopi larvae belong to the group of species with sclerites present on the pro-, meso-, and metanota. Because lateral setae on abdominal segment III are lacking and the larval case lacks a sand collar at its base, A. episkopi keys with Agapetus laniger Pictet 1834 and Agapetus delicatulus McLachlan 1884. Within this trio, each of the latter two species can be easily separated from A. episkopi by the coloration pattern of their frontoclypeus, where a pale central area is present, and by the presence of only one lateral seta on each side of abdominal segment I. With respect to distribution, A. episkopi has been recorded from European Ecoregion 6 (= Hellenic western Balkan region) and Asia Minor. In addition, ecological characteristics are briefly discussed, and a key to the known glossosomatid larvae of European Ecoregion 6 is included.